Neo-Platonic love in fictional obsessions - Castelli, Alberto (Verbum – Analecta Neolatina, 2023)
Twentieth-century novels present sexuality as a source of mystifying pleasure often challenging the conventions of heterosexual relationships by presenting a plot with elderly men captivated by much younger women. Alternatively, we should read those controversial texts as a Neo-Platonic exercise wherein Beauty itself recalls virtue and the more beautiful something is the more it is identifiable with the divine. Consequently, to those who managed to attain, by contemplation, the pure beauty, such contemplation would resemble a revelation of some sort. In the end, much the same way as plants naturally seek out sunlight, man before death reconciles all desires with a longing for God.